2010
DOI: 10.1002/jmri.22299
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sodium intensity and perfusion deficits in acute ischemic stroke

Abstract: Purpose: To assess the relationship between sodium signal intensity changes and oligemia, measured with perfusion-weighted imaging (PWI), in ischemic stroke patients. Materials and Methods:Nine ischemic stroke patients (55 6 13 years), four with follow-up scans, underwent sodium and proton imaging 4-32 hours after symptom onset. Relative sodium intensity was calculated as the ratio of signal intensities in core (identified as hypertintense lesions on diffusion-weighted imaging [DWI]) or putative penumbra (PWI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 33 publications
5
50
0
Order By: Relevance
“…10 Recent studies involving human sodium MRI in the acute stroke period showed that sodium signal levels measured in the core tissue, defined by visibly increased DWI signal, remained normal up to 7 hours after arterial occlusion before eventually increasing. 8,9 This is consistent with the current and previous 13,17 rat stroke studies, where variable delay times were measured before TSC increased, coupled with early small decreases in sodium levels in the penumbra, suggesting that any increase above normal levels (we propose this as a viability threshold level) would indicate irreversible damage. In this case, permanent tissue damage would not be directly correlated with SOT, that is, the time of arterial occlusion, but rather the time at which sodium signal begins to increase above normal levels.…”
Section: Tissue Sodium Signal To Predict Stroke Onset Timesupporting
confidence: 90%
See 1 more Smart Citation
“…10 Recent studies involving human sodium MRI in the acute stroke period showed that sodium signal levels measured in the core tissue, defined by visibly increased DWI signal, remained normal up to 7 hours after arterial occlusion before eventually increasing. 8,9 This is consistent with the current and previous 13,17 rat stroke studies, where variable delay times were measured before TSC increased, coupled with early small decreases in sodium levels in the penumbra, suggesting that any increase above normal levels (we propose this as a viability threshold level) would indicate irreversible damage. In this case, permanent tissue damage would not be directly correlated with SOT, that is, the time of arterial occlusion, but rather the time at which sodium signal begins to increase above normal levels.…”
Section: Tissue Sodium Signal To Predict Stroke Onset Timesupporting
confidence: 90%
“…Recent patient data indicate that the sodium signal remains unchanged in presumed penumbra tissue 8,9 and that sodium signal changes in the core do not reverse after reperfusion. 19 During acute stroke it has been reported that the lesion identified from increased sodium concentration can be smaller than the lesion identified from decreased ADC.…”
Section: Introductionmentioning
confidence: 99%
“…Taking these factors into consideration, in human stroke, a lag in the increase in 23 Na signal intensity has been identified with increases of less than 10% in the first 7 h increasing to 23% beyond 9 h and eventually leveling at 69% (7). A recent article reported no 23 increase in penumbral tissue as defined by the diffusion/perfusion-mismatch within 4-7 h after stroke onset (25). In the ischemic core (not defined as cortex or subcortex) in a rabbit embolic model, an acute (11%) decrease in signal during the first 40 min of ischemia was followed by a 12%/h increase, culminating in a 25% increase over baseline by 4 h poststroke (15).…”
Section: Discussionmentioning
confidence: 99%
“…The potential diagnostic benefits of 23 Na-MR imaging have recently been demonstrated for common pathological conditions such as tumor [5,6], stroke [7][8][9], Alzheimer disease [10], paramyotonia [11], arthritis [12], multiple sclerosis [13] and functional renal imaging [14] in humans. In addition, pre-clinical in vivo 23 Na MRI enables one to temporally follow pathological progression in animal models of common human disease [14][15][16].…”
Section: Introductionmentioning
confidence: 99%